Poetry in the Cypriot Dialect and Pavlos Liasides - Moleskis, Yiorgos (Études helléniques / Hellenic Studies, 2007)
After Vassilis Michaelides and Dimitris Lipertis, another poet, Pavlos Liasidis, used the Cypriot dialect, his poor education having prevented him from mastering the common Greek language. Raised in a rural milieu and nurtured by folk songs, he sings the joys and pains of rural life, and is deeply concerned about the social and political issues of his country.